Ludwig van Beethoven - Thompson, Wendy, 1952- (New York : Viking, 1991)
Introduces the life and works of the great composer, and sets him in the context of his times.
"First published in Great Britain by Faber & Faber Ltd in association with Faber Music Ltd, 1990"--P. 48.
"Ages 12 up"--Jacket.
Sch Libr Jnl
Publ Weekly
Kirkus
Keywords: Beethoven, Ludwig van, -- 1770-1827 -- Juvenile literature; Beethoven, Ludwig van, -- 1770-1827; Composers -- Biography -- Austria; Composers; Beethoven, Ludwig van, 1770-1827; Beethoven, Ludwig van, 1770-1827